Application Of Augered, Cast-In-Place Displacement (ACIPD) Piles In New York City - Willie M. NeSmith (Deep Foundations Institute, 2004)
Conventional augered, cast-in-place (ACIP) piles were introduced into the New York City area as a result of the damage to existing structures caused by pile driving operations. ACIP piles are often specified where deep foundations are to be installed adjacent to transit facilities, sensitive underground utilities or in close proximity to existing structures. However, loss-of-ground issues associated with the installation of ACIP piles have prevented the wide-scale use of these systems. Beginning in 2002, Berkel & Company Contractors, Inc. began using its augered, cast-in-place displacement (ACIPD) system in the New York City area. Like conventional ACIP piles, this system produces almost no vibration. Also, as almost no material is brought to the surface, there is no opportunity for loss of ground. This paper presents a description of Berkel's displacement pile system and a brief discussion of six projects in the New York City area that have been executed with this system over the past two years.